Numerical and experimental assessement of the displacement field on PDMS sample - Ribeiro, J.E. (2018)
In recent years, the study of polymers like polydimethylsiloxane materials (PDMS) has become a great interest field due its growing used in biomechanics applications. In this work the Digital Image Correlation (DIC) is proposed for the measurement of the continuous displacement field. This experimental optical technique allows the measurement with high resolution and without contact of the large displacements at the material surface and, therefore, is considered the most suitable technique for the mechanical characterization of hyper-elastic materials. The numerical simulations were implemented by using the commercial finite elements program Ansys®. This combines the experimental information taken from the tensile test performed in PDMS with material constitutive models to reproduce the experimental displacement fields observed during the experimental test. For this study, different constitutive hyper-elastic material models were analysed, namely: the Mooney- Rivlin model, Ogden model and Yeoh models. The numerical technique show to be very effective to reproduced the global mechanical behaviour of hyper-elastic materials. However, the local behaviour is very difficult to predict and further developments must be made in order to improve the quality of material behaviour.